The Processing of Coconut Oil into Solid Soap and Liquid Soap in Cangkarman Village, Bangkalan, Madura - Sintha Soraya Santi; Rosida (Nusantara Science and Technology Proceedings)
This community service activities aim to: 1) increase the ability of me3mbers to make solid soap and liquid soap; 2) increase partner knowledge of solid soap and liquid soap processing that can provide economic benefit; 3) increase partner understanding of financial analysis of the business. This community service implementation method is an empowerment model for partners, farmer women grup namely “Anggrek” in Cangkarman village, Bangkalan. The implementation methods used the following steps: 1) Discussion; 2) Training ; 3) Mentoring and Evaluation. The methods of community service are training, mentoring, and practice of making solid soap and liquid soap according to the basic formulation, marketing management, packaging, and labeling. The results obtained from this activity include: 1) partners can process coconut oil into solid soap and liquid soap 2) Partners have skill in the process of producing solid soap and liquid soap; 3) Partners understand the benefits of making solid soap and liquid soap for increasing family income.